Electrochemical Synthesis of Novel Zn-Doped TiO2 Nanotube/ZnO Nanoflake Heterostructure with Enhanced DSSC Efficiency - K, Aijo John; Naduvath, Johns; Mallick, Sudhanshu; Pledger, Jacob W.; Remillard, S. K.; DeYoung, P. A.; Thankamoniamma, Manju; Shripathi, T.; Philip, Rachel Reena (Nano-Micro Letters, 2016)
The paper reports the fabrication of Zn-doped TiO2 nanotubes (Zn-TONT)/ZnO nanoflakes heterostructure for the first time, which shows improved performance as a photoanode in dye-sensitized solar cell (DSSC). The layered structure of this novel nanoporous structure has been analyzed unambiguously by Rutherford backscattering spectroscopy, scanning electron microscopy, and X-ray diffractometer. The cell using the heterostructure as photoanode manifests an enhancement of about an order in the magnitude of the short circuit current and a seven-fold increase in efficiency, over pure TiO2 photoanodes. Characterizations further reveal that the Zn-TONT is preferentially oriented in [001] direction and there is a Ti metal-depleted interface layer which leads to better band alignment in DSSC.